Nanostructure and Microstructure Fabrication: From Desired Properties to Suitable Processes. Issue 20 (24th March 2018) - van Assenbergh, Peter; Meinders, Erwin; Geraedts, Jo; Dodou, Dimitra
Abstract: When designing a new nanostructure or microstructure, one can follow a processing‐based manufacturing pathway, in which the structure properties are defined based on the processing capabilities of the fabrication method at hand. Alternatively, a performance‐based pathway can be followed, where the envisioned performance is first defined, and then suitable fabrication methods are sought. To support the latter pathway, fabrication methods are here reviewed based on the geometric and material complexity, resolution, total size, geometric and material diversity, and throughput they can achieve, independently from processing capabilities. Ten groups of fabrication methods are identified and compared in terms of these seven moderators. The highest resolution is obtained with electron beam lithography, with feature sizes below 5 nm. The highest geometric complexity is attained with vat photopolymerization. For high throughput, parallel methods, such as photolithography (≈10 1 m 2 h −1 ), are needed. This review offers a decision‐making tool for identifying which method to use for fabricating a structure with predefined properties. Abstract : In this review, fabrication methods for nanostructures and microstructures are assessed based on the geometric and material complexity, resolution, total size, geometric and material diversity, and throughput they can achieve. In the design process of nanostructures and microstructures, this review facilitates making the step from envisioned performance (and consequently required properties and architecture) toward the most suitable fabrication methods.